ANALYZING AND FORECASTING CO₂ EMISSIONS IN THE ALUMINUM SECTOR USING ARIMA MODEL - Ramil Hasanov; Jamil Safarov; Arzu Safarli (Agora International Journal of Economical Sciences (AIJES), 2024)
The urgent and pressing challenge posed by global climate change underscores the critical need for immediate and decisive action, particularly in the mitigation of greenhouse gas (GHG) emissions to facilitate a trajectory towards sustainability. The significance of the aluminium industry, characterized by its notable carbon footprint, accentuates the importance of conducting comprehensive and environmentally conscious analyses within this sector. Heightened environmental apprehensions surrounding aluminium production necessitate the development of effective approaches for emission forecast. The primary aim of the article is to elucidate the present situation and future predictions of carbon emissions within the global aluminium industry, particularly in the context of escalating concerns regarding global climate security. The research concluded that there will be a decrease in CO2 emissions within the aluminium industry in the future as a result. Through meticulous assessments and exhaustive forecasts of CO2 emissions across the global aluminium industrial chain system, this study employed the Autoregressive Integrated Moving Average (ARIMA) model to scrutinize data spanning from 2005 to 2030. By furnishing valuable insights into prospective emission patterns and providing guidance for the formulation of sustainable policy measures, this research assumes a pivotal role in shaping data-driven strategies aimed at mitigating the environmental impact of aluminum production. Consequently, it contributes significantly to the collective endeavor to combat climate change and foster a more resilient and sustainable future for humanity.
Keywords: 330